Identifikasi Karakteristik Daerah Aliran Sungai dan Kemampuan Lahan untuk Menyusun Arahan Penggunaan Lahan pada Sub Das Gunggung - SURYADI, I MADE ADI; WIYANTI, WIYANTI; DIBIA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Identification of Watershed Characteristics and Land Capability for Land Use Direction in Gunggung Sub-Watershed Gunggung Sub Watershed is upstream of Jinah Watershed and included in the Oos Jinah Unit Management Area Watershed, which has function and important role in supporting community water needs in Bangli and Karangasem Regency.This study aims to determine the characteristics, land capability classes, land use direction and proper management actions to keep the function of the land remains sustainable and continuous. A method used is survey and observation. Watershed characteristic is determined by digitally and landuse is determined by scoring.The result of this study showed that in Gunggung Sub Watershed there were VI and VII land capability classes and based on the results of land use scoring, land is directed into protected area and buffer area with limiting factor is texture and water retention capacity. Land management like improvements the terrace, addition of organic matter, increase plant density, planting ground cover and planting layered header system will increase the land capability classes. Land use recommended after management is mixed plantation high density with forest plants (unit 1, 2, 6, 13, and 14), mix plantation high density with patio bench contruction (unit 3, 8, 10, 11, 12, 15, 16 and 17), the cultivation of seasonal and perennial crops (unit 4 and 5), the cultivation of perennial crops (unit 7) and cultivation of seasonal crops (unit ).
Keywords: Watershed Characteristics; Land Capabilitie; and Watershed Land Use Direction